Valproate-Induced Congenital Malformations - J Gordon Millichap (Pediatric Neurology Briefs)
The risk of congenital malformations in infants of women with epilepsy treated with antiepileptic drugs (AEDs) during the first trimester of pregnancy and in those whose mothers had discontinued AEDs before pregnancy was compared in a study at the Universities of Tampere and Oulu, Finland.